Penurunan Kadar Torium dan Radioaktivitas dalam Limbah Cair Proses Pengolahan Monasit PLUTHO Menggunakan Koagulan FeSO4 - Marisi, Dany Poltak; Suprihatin; Ismayana, Andes (EKSPLORIUM, 2018)
The separation of radioactive and rare earth mineral carried out in PLUTHO produces waste that still contains thorium and uranium. The resulting waste requires further processing to be environmentally friendly. The purpose of study is to reduce thorium content and radioactivity in liquid waste of PLUTHO monazite treatment process using ferro sulphate coagulant. PLUTHO Pilot Plant is one of facility that built to dissociate uranium, thorium and light rare earth from mineral of monazite. Variations of treatments applied in the research are coagulant dosage and pH. Thorium content is measured by Spectrophotometer UV-Vis method, whereas radioactivity is measured by radiation counting meter Ludlum Model 1000 Scaler. The result shows that the optimum condition of coagulation is in pH 8,0 with concentration of ferro sulphate 225 mg/L which may reduce thorium content up to 45,20 % and reduce radioactivity to 100 % out of its initial thorium content and radioactivity as much as 0,73 mg/L and 1,35 Bq/g, respectively.